53.8k views
0 votes
Which of the following steps would you perform to the system of equations below so that the equations have equal x coefficients? 4x+2y=4 12x+y=22 A. Multiply both sides of the top equation by 3 B. Divide both sides of the top equation by 3 C. Divide both sides of the bottom equation by 2 D. Multiply both sides of the bottom equation by 3​

User Giorgio
by
6.2k points

1 Answer

6 votes
Answer: A.

Step-by-step explanation:
By multiplying the top equation by 3, you now have

12x + 6y = 12
12x + y = 22

To completely solve the equation, you multiply the whole bottom equation by -1.

12x + 6y = 12
-12x - y = -22

The -12x and 12 x cancel each other out.

6y = 12
-y = -22
______
5y = -10
y = -2


Now that you have the value of y, you can plug it into the original equation.

4x + 2y = 4
4x + 2(-2) = 4
4x - 4 = 4
4x = 8
x = 2

So, your final answer is (2, -2).
User Roman Skydan
by
7.1k points